The Impact of Economic Contractions on the Effectiveness of R&D and Advertising: Evidence from U.S. Companies Spanning Three Decades - Steenkamp, Jan-Benedict E. M.; Fang, Eric (Er) (Marketing Science, 2011)
The critical role of research and development (R&D) and advertising in the marketing strategy of the firm is well established. This paper conceptually and empirically examines why and how much the effectiveness of these two marketing instruments differs between times of economic expansions versus periods of economic contractions—and whether these results depend on the cyclicality of the industry in question. We consider a key marketing metric (market share) and a key financial metric (firm profit). Our empirical setting is 1,175 U.S. firms across a time period spanning over three decades. We find that R&D and advertising contribute to firm performance but that their effectiveness is not constant across the business cycle. Increasing advertising share in contractions has a stronger effect on profit and market share than increasing advertising share in expansions. Likewise, investments in R&D in contractions lead to higher gains in market share and profit than R&D investments in expansions, albeit only in subsequent years. If in contractions the firm faces tight budget constraints and has to choose between either maintaining R&D or advertising, our simulation results show that maintaining R&D is associated with better company performance. We find that advertising effectiveness, in general, and in contractions, in particular, is systematically moderated by the degree of cyclicality of the industry in which the firm operates. In relatively stable industries, advertising effects are small or even nonsignificant, and they do not go beyond the year the firm advertises. However, in highly cyclical industries, advertising effects are long-lasting, its total effect being 50% larger (market share) and 200% larger (profits) than in industries of average cyclicality. The effect of industry cyclicality on advertising effectiveness is especially pronounced in contractions. Collectively, these findings provide valuable and actionable insights into how firms should respond to contractions in order to grow profits and market share.